Di(Thioether Sulfonate)‐Substituted Quinolinedione as a Rapidly Dissoluble and Stable Electron Mediator and Its Application in Sensitive Biosensors. Issue 2 (7th November 2021) - Nandhakumar, Ponnusamy; Lee, Woohyeong; Nam, Sangwook; Bhatia, Aman; Seo, Jia; Kim, Gyeongho; Lee, Nam‐Sihk; Yoon, Young Ho; Joo, Jung Min; Yang, Haesik
Abstract: The commonly required properties of diffusive electron mediators for point‐of‐care testing are rapid dissolubility, high stability, and moderate formal potential in aqueous solutions. Inspired by nature, various quinone‐containing electron mediators have been developed; however, satisfying all these requirements remains a challenge. Herein, a strategic design toward quinones incorporating sulfonated thioether and nitrogen‐containing heteroarene moieties as solubilizing, stabilizing, and formal potential‐modulating groups is reported. A systematic investigation reveals that di(thioether sulfonate)‐substituted quinoline‐1, 4‐dione (QLS) and quinoxaline‐1, 4‐dione (QXS) display water solubilities of ≈1 m and are rapidly dissoluble. By finely balancing the electron‐donating effect of the thioethers and the electron‐withdrawing effect of the nitrogen atom, formal potentials suitable for electrochemical biosensors are achieved with QLS and QXS (−0.15 and −0.09 V vs Ag/AgCl, respectively, at pH 7.4). QLS is stable for >1 d in PBS (pH 7.4) and for 1 h in tris buffer (pH 9.0), which is sufficient for point‐of‐care testing. Furthermore, QLS, with its high electron mediation ability, is successfully used in biosensors for sensitive detection of glucose and parathyroid hormone, demonstrating detection limits of ≈0.3 × 10 −3 m and ≈2 pg mL −1, respectively. This strategy produces organic electron mediators exhibiting rapid dissolution and high stability, and will find broad application beyond quinone‐based biosensors. Abstract : This study demonstrates that di(thioether sulfonate)‐substituted quinoline‐1, 4‐dione is an efficient electron mediator with high water solubility, rapid dissolubility, high stability, and moderate formal potential suitable for point‐of‐case testing. When this mediator is applied in a couple of biosensors for glucose and parathyroid hormone, sensitive detection is achieved owing to its high electron mediation ability.